Prevalence and trends in hypertension in Andhra Pradesh - Reddy, Sagam Dinesh (International Journal Of Community Medicine And Public Health, 2025)
Hypertension is a significant public health concern globally, contributing to cardiovascular diseases, stroke, and kidney failure. Andhra Pradesh, a southern state in India, has witnessed rapid urbanization and lifestyle changes, potentially influencing hypertension prevalence. This cross-sectional study, conducted at LMR hospital, G Konduru, from January 2022 to December 2023, analyzed data from national health surveys (NFHS, DLHS), state health department records, and published research studies. Findings revealed a significant increase in hypertension prevalence over the last three decades, particularly among urban residents, elderly populations, and males. Urbanization, dietary changes, and sedentary lifestyles were identified as key contributors. Public health interventions had a modest impact on controlling hypertension rates. Comprehensive strategies, including awareness programs and improved healthcare services, are essential for effective hypertension management in Andhra Pradesh.